PENANGANAN PERCERAIAN AKIBAT KEKERASAN DALAM RUMAH TANGGA (KDRT) MELALUI PENERAPAN UU NO. 23 TAHUN 2004 DI KABUPATEN ROKAN HILIR - Ramadhan Syahmedi, Juhari Muslim, Hafsah, (AT-TAFAHUM: Journal of Islamic Law, 2017)
Abstract: The reseach results obtained are the causes of divorce in Rokan Hilir distric increased due to the occurrence of relationships, as the theory used is the lack of attention to the spouse, differences in education knowledge, and lack of mutual, know the husband and wife both financial and their respective strengths, so they always demand and lackself-evalution of each other. Domestic violence in Rokan Hilir regency is physical, physical, sexual and economic violence. Like the case that was scrutinized in the abused and beaten as for the other cases in spit on the husband because they have the same hard nature and the absence of succumbing to each other. Physical and emotionalviolence among them is the traumatic experienced by victims due to other acts of violence. Violence in Rokan Hilir is the main cause of divorce in Rokan Hilir. Handling of divorce on the grounds of domestic violence uses UU No. 23 0f 2004 in both the religius courts and both criminal and procedural law. The implementation of the handling of divorce in the downstream Rocan district community teaches the community that that the nature of marriage is the opposite of the purpose of perfectingpart of religion in the way of Allah and seeking its blessing, as well as learning the procedures in the religious court.Kata Kunci: Penanganan, Cerai Gugat, Masyarakat Muslim, UU NO 23 Tahun 2004